2014
DOI: 10.1007/s10549-014-3159-4
|View full text |Cite|
|
Sign up to set email alerts
|

Generation of MCF-7 cells with aggressive metastatic potential in vitro and in vivo

Abstract: Epithelial-mesenchymal transition (EMT) is a cellular development program characterized by loss of cell adhesion and increased cell mobility. It is essential for numerous processes including metastasis. In this study we have generated "aggressive" MCF-7 breast cancer cells (MCF-7-EMT), which show significantly increased invasion in contrast to wild type MCF-7 (MCF-7 WT) cells. In addition, we have analyzed, whether these cell lines differ in their metastatic behavior in vivo and in expression of invasion and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 17 publications
2
44
0
Order By: Relevance
“…33,34 Exosomes from MCF7 cells or MCF7 cells treated with PMA to increase their malignant potential failed to display thrombotic activity with fibrinogen or human platelet-poor plasma (supplemental Figure 1B). However, thrombotic activity was detected with MVs from MCF7 cells with fibrinogen or human platelet-poor plasma (supplemental Figure 1A), whereas MVs from PMA-treated MCF7 cells displayed thrombotic activity only in the presence of fibrinogen (supplemental Figure 1A).…”
Section: Thrombotic Activity Of Exosomes and Mvsmentioning
confidence: 99%
“…33,34 Exosomes from MCF7 cells or MCF7 cells treated with PMA to increase their malignant potential failed to display thrombotic activity with fibrinogen or human platelet-poor plasma (supplemental Figure 1B). However, thrombotic activity was detected with MVs from MCF7 cells with fibrinogen or human platelet-poor plasma (supplemental Figure 1A), whereas MVs from PMA-treated MCF7 cells displayed thrombotic activity only in the presence of fibrinogen (supplemental Figure 1A).…”
Section: Thrombotic Activity Of Exosomes and Mvsmentioning
confidence: 99%
“…Rif is distantly related to other GTPases (32-49% identity), but retains the common switch 1 and 2 regions that allows the function of small GTPases. The mechanism of Rif induced filopodia has been studied by Goh et al (2011), who showed a direct interaction of Rif with mDia1 without involving the Cdc42 effectors N-WASP In a recent study (Ziegler et al, 2014), MCF7 cells with increased invasiveness ("aggressive" MCF7) were selected, but these cells did not express podoplanin. In another study with MCF7 cells, Yang and Kim (2014) showed that inhibition of ROCK activity leads to MCF7 cells activation, with loss of epithelial characteristics (loss of cell junctions, loss of E-cadherin and β-catenin in the membrane and increased proliferation, migration and invasion).…”
Section: Podoplanin and Emtmentioning
confidence: 99%
“…For better clearness invasion is shown as % of control (=100 %). Actual numbers of invaded cells of different human breast cancer cell lines were published by Ziegler et al [20].…”
Section: Co-culture and Microinvasion Assaymentioning
confidence: 99%
“…Mesenchymal transformed MCF-7 cells (MCF-7-EMT) were generated as described by Ziegler et al [20]. Briefly, single-cell suspensions of wild type MCF-7 cells (MCF-7 WT) were suspended at a density of 40,000 cells/mL in DMEM/F-12 containing 5 lg/mL insulin (Sanofi-Aventis, Frankfurt, Germany), 0.5 mg/mL hydrocortisone, 2 % B27 supplement (Invitrogen, Darmstadt, Germany), 20 ng/mL epidermal growth factor (EGF; Sigma, Deisenhofen, Germany), 20 ng/ml fibroblast growth factor-2 (FGF-2; Sigma), and 1 % penicillin/streptomycin (PAA Laboratories) before incubation on ultralow adherence six-well plates (2.5 mL/plate; Corning, Lowell, MA, USA).…”
Section: Generation Of Aggressive Mcf-7 Cellsmentioning
confidence: 99%
See 1 more Smart Citation